Can ESG Reduce Credit Risk? An Empirical Investigation Across ASEAN-5 Markets - Zaini, Arrafif Pratama; Ulpah, Maria (The Indonesian Capital Market Review, 2025)
Based on stakeholder theory and signaling theory, companies with strong ESG performance send signals to various stakeholders, thus building trust and influencing better credit risk evaluation. This study empirically examines the effect of Environmental, Social, and Governance (ESG) performance on the credit risk of non-financial public companies in ASEAN-5 countries (Indonesia, Malaysia, Philippines, Singapore, and Thailand) over the period 2019-2023. Corporate credit risk is measured using 2 main approaches: the accounting-based and market-based models. Merton's KMV model calculates the probability of default (PD) using a market-based approach. In contrast, the Altman Z-Score predicts bankruptcy risk based on financial ratios in the accounting-based approach, providing a solid framework for evaluating credit risk. These findings suggest that environmental sustainability and good governance are the main factors that drive the reduction of credit risk in ASEAN-5. It has different implications from previous research on social initiatives that do not reflect credit risk.